'Life' in Theological Education and Missional Formation: A Reflection for a New Christian Era. (January 2016) - Ma, Wonsuk
The third Christian millennium has dawned and global Christianity has been making a drastic shift from the north to the south. This also coincides with the beginning of the post-Christendom era. How these two mega shifts would impact theological education and missional formation is an active discussion today. The study, intended to be a preliminary conversation starter, is a reflection of a southern Christian. It identifies three major components ('world', 'mission' and 'life') that have been developed, altered, or even dropped in the Christendom process, and how the new era affords world Christianity with a rare opportunity to evaluate, revision, and restore the vision of theologising and theological formation. A fourth component ('Evangelical Christian experience') is added to counter-balance the de-Christendom attempts that took place in the twentieth century, which also illustrates the complexity of, and the limitation to, the argument that is presented here.